Условия разрядноимпульсного инициирования и параметры процесса самораспространяющегося высокотемпературного синтеза углеродных наноматериалов - Челпанов, Дмитрий Ильич; Бакларь, Виктор Юрьевич; Кускова, Наталья Ивановна; Корзинова, Анна Николаевна (НТУ "ХПИ", 2016)
Получены аналитические зависимости параметров разрядного контура от термодинамических характеристик порошковых систем исходных реагентов. Рассчитаны электротехнические параметры для инициирования процесса самораспространяющегося высокотемпературного синтеза углеродных наноматериалов в системах порошков составами алюминий + политетрафторэтилен и алюминий + политетрафторэтилен + железо. Проведены экспериментальные исследования процесса самораспространяющегося высокотемпературного синтеза в выбранных порошковых системах. Построены температурные профили для волн горения в выбранных порошковых системах, которые представлены в виде зависимостей теплового потока от температуры и температуры от времени.

Analytical dependencies of electrical discharge circuit’s parameters on thermodynamic characteristics of powder systems of initial reagents were obtained. Electrotechnical parameters for the initiation of the process of self-propagating high-temperature synthesis of carbon nanomaterials in general in powder system of aluminum + polytetrafluorethylene and carbon nanotubes specifically in powder system aluminum + polytetrafluorethylene + iron with iron used as a known nanotubes catalyst were calculated.Experimental researches of the process of self-propagating high-temperature synthesis of carbon nanomaterials in chosen powder systems were conducted. Thermal profiles consisting of dependencies of thermal flow on temperature and temperature on time for combustion waves in chosen powder systems were formed based on the experimental data about combustion wave’s parameters and calculated parameters of initial powders systems.
Conditions for the pulse discharge initiation and parameters of the process of self-propagating high-temperature synthesis of carbon nanomaterials
Keywords: электроразрядный контур; углеродные нанотрубки; УНМ; СВС; electrical discharge circuit